Evaluating N‐difluoromethyltriazolium triflate as a precursor for the synthesis of high molar activity [18F]fluoroform. (20th September 2021) - Pees, Anna; Vosjan, Maria J. W. D.; Chai, Jin Young; Cha, Hyojin; Chi, Dae Yoon; Windhorst, Albert D.; Vugts, Danielle J.
Abstract : The trifluoromethyl group is a prominent motif in biologically active compounds and therefore of great interest for the labeling with the positron emitter fluorine‐18 for positron emission tomography (PET) imaging. Multiple labeling strategies have been explored in the past; however, most of them suffer from low molar activity due to precursor degradation. In this study, the potential of 1‐(difluoromethyl)‐3‐methyl‐4‐phenyl‐1 H ‐1, 2, 3‐triazol‐3‐ium triflate as precursor for the synthesis of the [ 18 F]trifluoromethylation building block [ 18 F]fluoroform with high molar activity was investigated. The triazolium precursor was reacted under various conditions with [ 18 F]fluoride, providing [ 18 F]fluoroform with radiochemical yields (RCY) and molar activities ( A m ) comparable and even superior with already existing methods. Highest molar activities ( A m = 153 ± 14 GBq/μmol, dc, EOS) were observed for the automated procedure on the Neptis® perform module. Due to its easy handling and good RCY and A m in the [ 18 F]fluoroform synthesis, the triazolium precursor is a valuable alternative to already known precursors. Abstract : This article describes the evaluation of N ‐difluoromethyltriazolium triflate as a new precursor for high molar activity [ 18 F]fluoroform. The triazolium precursor was reacted under various conditions with [ 18 F]fluoride, providing [ 18 F]fluoroform with good radiochemical yields and high molar activities.